Detection and isolation of human serum autoantibodies that recognize oxidatively modified autoantigens. - Eggleton, P; Nissim, A; Ryan, B; Whiteman, M; Winyard, P (2013)
The breakdown of human immune tolerance to self-proteins occurs by a number of mechanisms, including posttranslational modifications of host molecules by reactive oxygen, nitrogen, or chlorine species. This has led to great interest in detecting serum autoantibodies raised against small quantities of oxidatively modified host proteins in patients with autoimmune inflammatory diseases, such as rheumatoid arthritis. Here, we provide protocols for the preparation and chemical characterization of oxidatively modified protein antigens and procedures for their use in immunoblotting and ELISAs that detect autoantibodies against these antigens in clinical samples. These gel electrophoresis- and plate reader-based immunochemical methods sometimes suffer from low analytical specificity and/or sensitivity when used for serum autoantibody detection. This is often because a single solid-phase protein (antigen) is exposed to a complex mixture of serum proteins that undergo nonspecific binding. Therefore more sensitive/specific techniques are required to detect autoantibodies specifically directed against oxidatively modified proteins. To address this, we describe novel affinity chromatography protocols by which purified autoantibodies are isolated from small volumes (<1 ml) of serum. We have also developed strategies to conjugate submilligram amounts of isolated immunoglobulins and other proteins to fluorophores. This set of methods will help facilitate the discovery of novel diagnostic autoantibodies in patients.